Implikasi Kebijakan Penghentian Perjanjian Investasi Bilateral Indonesia terhadap Penyelesaian Sengketa Investasi melalui Mekanisme Arbitrase Internasional - Dini Sofia Laeliyah; Fithriyatirrizqoh Fithriyatirrizqoh; Sang Ayu Putu Rahayu (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines Indonesia's policy of terminating Bilateral Investment Treaties (BITs) and its implications for foreign investors' access to international arbitration mechanisms. The increasing number of international investment disputes, particularly the Churchill Mining Plc v. Republic of Indonesia case demanding USD 2 billion in compensation, prompted Indonesia to conduct a comprehensive review and terminate more than 60 BITs with over 50 countries starting in 2014. This research employs a normative juridical method using statute, conceptual, and case approaches, with primary legal materials comprising Bilateral Investment Treaties, the ICSID Convention, and national legislation, supplemented by secondary materials from relevant academic literature. The study finds that Indonesia's BIT termination was driven by three principal factors: substantive imbalance in first-generation BITs that excessively favored investor protection over the state's regulatory space, the ISDS mechanism's structural bias toward investors that posed significant financial and reputational risks, and the need to reform Indonesia's international investment legal framework to better reflect contemporary national interests. Regarding its implications, BIT termination eliminates the pactum de compromittendo that serves as the jurisdictional basis for ICSID arbitration under Article 25(1) of the ICSID Convention, thereby closing foreign investors' direct access to international arbitration for new investments. However, survival Clauses in most terminated BITs continue to protect existing investments for 10–15 years post-termination.